2001
DOI: 10.1159/000051874
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Proliferation and Delayed Intestinal Transit in a Patient with a GLP-1-, GLP-2- and PYY-Producing Neuroendocrine Carcinoma

Abstract: Glucagon-like peptides (GLP) 1 and 2 are hormones derived from the post-translational processing of proglucagon in the intestinal L cells that influence intestinal motility and small bowel growth, respectively. We describe a patient with a neuroendocrine tumor of unknown primary origin with peritoneal carcinomatosis and diffuse liver metastases, who presented with constipation and nocturnal itching for over 3 years. Small bowel follow-through showed decreased small intestinal motility and marked intestinal hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 22 publications
4
24
0
Order By: Relevance
“…This mechanism is consonant with the GLP1 capacity of delaying gastrointestinal transit not only in humans but also in rodents (Tolessa et al 1998a,b, Näslund et al 2001, Miki et al 2005, Schirra et al 2009, Hellström 2011. Moreover, our results could provide a mechanistic explanation for the observations that GLP1-secreting tumors are associated with severe constipation and delayed colonic transit (Byrne et al 2001, Brubaker et al 2002), and for the constipation observed in prolonged treatment with liraglutide (Jeong & Yoo 2011). Our finding seem in contrast with previous findings that showed weak contractions in response to GLP1 in isolated circular smooth muscle cells from the human colon, which are likely due to an increase in the availability of glucose energy (Ayachi et al 2005).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This mechanism is consonant with the GLP1 capacity of delaying gastrointestinal transit not only in humans but also in rodents (Tolessa et al 1998a,b, Näslund et al 2001, Miki et al 2005, Schirra et al 2009, Hellström 2011. Moreover, our results could provide a mechanistic explanation for the observations that GLP1-secreting tumors are associated with severe constipation and delayed colonic transit (Byrne et al 2001, Brubaker et al 2002), and for the constipation observed in prolonged treatment with liraglutide (Jeong & Yoo 2011). Our finding seem in contrast with previous findings that showed weak contractions in response to GLP1 in isolated circular smooth muscle cells from the human colon, which are likely due to an increase in the availability of glucose energy (Ayachi et al 2005).…”
Section: Discussionsupporting
confidence: 85%
“…Few studies have analyzed the role of GLP1 in the regulation of colonic contractility, and the results remain controversial because both GLP1 stimulatory (Gülpinar et al 2000, Ayachi et al 2005 and inhibitory (Byrne et al 2001, Amato et al 2010 effects have been described. Interestingly, constipation has been reported among the side effects in treatment with liraglutide, a human GLP1R agonist, successfully used for the treatment of type 2 diabetes mellitus (Seino et al 2010, Jeong & Yoo 2011.…”
Section: Introductionmentioning
confidence: 99%
“…However, severe hypoglycemia is not always associated with GLP1 tumor secretion. In fact, two other patients with GLP1-and GLP2-producing NETs and with the absence of symptomatic hypoglycemia have been previously reported (86,87). …”
Section: Mechanisms Other Than Excess Insulinmentioning
confidence: 98%
“…This finding corresponds to the fact that, although these hamartomatous polyps themselves do not have malignant potential, patients with the syndrome must have an increased risk of developing adenocarcinoma (7)(8)(9)(10). When gastrointestinal adenocarcinoma occurs, it probably arises from coincidental adenomatous lesions that we have observed inside the polypous bulk surrounding the largest ileal polyp.…”
Section: Discussionmentioning
confidence: 83%